Treatment options for hypersensitivity of teeth affected with Molar-Incisor Hypomineralization: Literature Review - Navarro-Betetta, Rossmary (2023)
Purpose: To review information regarding to options for hypersensitivity of teeth affected with Molar-Incisor Hypomineralization (MIH). Material and Methods: A bibliographic search was carried out in the Scopus, PubMed/Medline and SciELO databases. The terms “Molar-incisor Hypomineralization”, “Dental Hypersensitivity” and “Treatment” were used for search. The selection criteria included articles published in Spanish, Portuguese, and English languages published in the last 10 years. Case reports, cross-sectional studies, case-controls, and randomized clinical trials were included. According to the presence of duplicates, and inclusion criteria, 14 articles were included in the review. Conclusion: Dental hypersensitivity associated with Molar-Incisor Hypomineralization (MIH) can be controlled by remineralizing and desensitizing agents such as fluoride, CPP-ACP, hydroxyapatite, and arginine-based pastes, resinous and ionomeric sealants, infiltrating resins, and high-power laser photobiomodulation therapies.